The book of horsemanship - Duarte, King of Portugal, 1391-1438 (Boydell and Brewer, 2016)
Written around 1430, Duarte of Portugal's remarkable treatise on chivalric horsemanship, the Livro do Cavalgar (Book on Riding), is the sole substantial contemporary source to survive on the definitive physical skill of the medieval knight. It also stands out from the body of technical writings of the Middle Ages for its intelligence, insight, and intellectual versatility, ranging from psychological reflections on horsemanship and its implications for human ethics, to the details of how to couch a lance under the arm without getting it caught on armour. Under the general rubric of horsemanship Duarte covers a range of topics that include jousting, tourneying, and hunting, as well as the physical apparatus of equestrianism and various cultural styles of riding. --Jacket.